2009
DOI: 10.1021/jp806842f
|View full text |Cite
|
Sign up to set email alerts
|

Ferrous Iron Reduction of Superoxide, A Proton-Coupled Electron-Transfer Four-Point Test

Abstract: Nelsen's four-point method of separating oxidants and reductants has been tested to evaluate its applicability to proton-coupled electron-transfer reactions. An efficient computational method was developed to determine rate-limiting steps in complex, multistep redox reactions. Geochemical redox reactions are rarely single-step, and by identifying the rate-limiting steps, computational time can be greatly reduced. The reaction of superoxide and ferrous oxide was selected as a test case for its simplicity and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…They also showed that both an increase and a decrease in driving force result in asymmetric parabolic functions for the transferring proton, which leads to greater contributions from excited vibrational levels, leading to a maximization of the KIE when the driving force is near zero. Wander and co-workers have utilized Nelsen’s four-point methodology, which involves separate calculation of reorganization energies of oxidants and reductants to estimate relative barrier heights and isotope effects for Fe 2+ reduction of superoxide by EPT …”
Section: Theory Behind Pcet and Eptmentioning
confidence: 63%
“…They also showed that both an increase and a decrease in driving force result in asymmetric parabolic functions for the transferring proton, which leads to greater contributions from excited vibrational levels, leading to a maximization of the KIE when the driving force is near zero. Wander and co-workers have utilized Nelsen’s four-point methodology, which involves separate calculation of reorganization energies of oxidants and reductants to estimate relative barrier heights and isotope effects for Fe 2+ reduction of superoxide by EPT …”
Section: Theory Behind Pcet and Eptmentioning
confidence: 63%
“…The solvent contributions are expected to be similar for all the reactions analyzed here because of the similar size of the phenol–pyridines. The calculations of λ i (sCPET) followed Nelson’s four-point method for ET reorganization energies, , with the proton transfer included in the reorganization energy, as we and others have done previously. The energies of the neutral molecule and radical cation (denoted E 0 and E + , respectively) are calculated at the optimized neutral and cation geometries (denoted ng and cg, respectively), and λ i (sCPET) is taken as the sum of the neutral and cation relaxation energies (denoted E relax 0 and E relax + , respectively) .…”
Section: Resultsmentioning
confidence: 99%
“…Wander and co-workers have utilized Nelsen's four-point methodology, which involves separate calculation of reorganization energies of oxidants and reductants 59 to estimate relative barrier heights and isotope effects for Fe 2+ reduction of superoxide by EPT. 60…”
Section: Kinetic Isotope Effect (Kie)mentioning
confidence: 99%